Use of Okadaic Acid to Identify Relevant Phosphoepitopes in Pathology: A Focus on Neurodegeneration - Jesús Avila; Miguel Medina; Nieves Villanueva (Marine Drugs, 2013)
Protein phosphorylation is involved in the regulation of a wide variety of physiological processes and is the result of a balance between protein kinase and phosphatase activities. Biologically active marine derived compounds have been shown to represent an interesting source of novel compounds that could modify that balance. Among them, the marine toxin and tumor promoter, okadaic acid (OA), has been shown as an inhibitor of two of the main cytosolic, broad-specificity protein phosphatases, PP1 and PP2A, thus providing an excellent cell-permeable probe for examining the role of protein phosphorylation, and PP1 and PP2A in particular, in any physiological or pathological process. In the present work, we review the use of okadaic acid to identify specific phosphoepitopes mainly in proteins relevant for neurodegeneration. We will specifically highlight those cases of highly dynamic phosphorylation-dephosphorylation events and the ability of OA to block the high turnover phosphorylation, thus allowing the detection of modified residues that could be otherwise difficult to identify. Finally, its effect on tau hyperhosphorylation and its relevance in neurodegenerative pathologies such as Alzheimer’s disease and related dementia will be discussed.